Description of two new Acanthoderini, and description of the male of Oreodera advena Martins & Galileo (Coleoptera, Cerambycidae, Lamiinae) - Santos-Silva, Antonio; de L. Nascimento, Francisco Eriberto; Júnior, José Osvaldo Silva (Zootaxa, 2020)
Two new species of Acanthoderini are described: Aegomorphus antonkozlovi, from Peru; and Plistonax antonkozlovi, from Panama. The male of Oreodera advena Martins & Galileo, 2005 is described for the first time, and a new Colombian department record is provided.